2016
DOI: 10.2458/azu_itet_v4i1_mcneil
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Teachers for Hybrid and Online Language Instruction

Abstract: Courses that are offered fully or partially online are becoming increasingly common for various reasons including needs for more flexibility and the affordances that technology can offer. One major challenge is that most of today's instructors did not learn online themselves and thus need to learn how to teach effectively using technology. This growing online trend is also true for language teaching, an area which demands special consideration due to its unique challenges: language teaching involves skill deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The application of this newly promoted module into teacher training programs offers flexible professional learning formats and may generate teacher readiness for instructional practice [6,47]. Researchers suggested that language teachers involve themselves as learners toward blended learning with an aim to effectively infuse this approach into classroom instruction in this digital era (e.g., [31,44]). While a few pioneering studies investigated blended trainings in preservice or inservice language education programs (e.g., [4,45,71]), they mostly documented how teachers perceived this learning approach or personal development of pedagogical and content knowledge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of this newly promoted module into teacher training programs offers flexible professional learning formats and may generate teacher readiness for instructional practice [6,47]. Researchers suggested that language teachers involve themselves as learners toward blended learning with an aim to effectively infuse this approach into classroom instruction in this digital era (e.g., [31,44]). While a few pioneering studies investigated blended trainings in preservice or inservice language education programs (e.g., [4,45,71]), they mostly documented how teachers perceived this learning approach or personal development of pedagogical and content knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…While a few pioneering studies investigated blended trainings in preservice or inservice language education programs (e.g., [4,45,71]), they mostly documented how teachers perceived this learning approach or personal development of pedagogical and content knowledge. It is hence important to further investigate the effectiveness of blended language teacher training on instructional practice as recent researchers underscore the significance of preparing teachers for hybrid language education to enhance student learning outcome (e.g., [1,44]).…”
Section: Introductionmentioning
confidence: 99%